Effective SERS substrate obtained by Au deposition at silica surfaces through a top down method - Damin, A.; Ivanchenko, P.; Fabbiani, M.; Martra, G. (Biophysical Bulletin, 2020)
Background: In the last years some of us developed methods for preparing, through simple synthesis protocols, gold nanoparticles supported on silica surfaces: in that cases, bottom-up approaches has been adopted (i.e. starting from HAuCl4 precursor) and high surface area silica (Aerosil 300) was chosen as support (together with controlled pH conditions), to facilitate Au dispersion. The obtained substrates showed the ability to enhance Raman signals of dosed molecules pyridine and bi-pyridine and/or of silanols species populating the silica surface. Following this idea, in this paper we will present results concerning surface-enhanced Raman spectroscopy (SERS) activity of substrates obtained by a top-down technique (i.e. gold sputtering) which allowed depositing gold nanoparticles at surfaces of silica nanoparticles. Pyridine molecule has been then used as a probe molecule to estimate the SERS activity of the obtained substrates.Objectives: The purpose of the work was to study the SERS activity of the prepared substrates through the estimation of limit of detection (LoD) of pyridine molecule dosed from solutions (benzene was used as solvent) with decreasing pyridine concentration.Materials and methods: For the preparation of the samples AOX50 silica (Evonik Industries, surface area of 50 m2/g) in form of pressed disk, a gold target and a K575X Turbo Sputter Coater (Quorum Technologies) were used. Methods applied: UV-Vis-NIR spectroscopy; HR-TEM microscopy; Raman spectroscopy.Results: Prepared Au/AOX50 substrates with nominal Au thickness 10 nm were characterized by the UV-Vis spectroscopy and HR-TEM microscopy. They showed a relatively complex absorption profile extending to the NIR region. The substrates contained gold nanoparticles with diameter in the range of 2.0–3.5 nm. By using the 785 nm exciting laser line (suggested by the results coming from UV-Vis spectroscopy) for recording Raman spectra, it was possible to observe characteristic pyridine Raman signals by contacting Au/AOX50 substrates with vapour phase of benzene solutions with pyridine concentration as low as 10-7 M comprising LoD. This allowed us to estimate roughly an enhancement factor of 108, as compared with 12.4 M pyridine dosed at naked AOX50 silica surface.Conclusion: Through a top-down technique it was possible to prepare effective SERS substrates composed by Au nanoparticles dispersed at AOX50 silica surfaces. LoD for pyridine dosed from the vapour of its benzene solution appeared to be 10-7 M and the SERS enhancement factor, using as a reference Raman spectra of 12.4 M pyridine interacting with naked AOX50 silica, has been estimated to be approximately 108.